The use of agricultural and livestock chemical products in the cattleranching area of Xico, central Veracruz, Mexico, and their possible environmental impact - Martínez M., Imelda; Cruz R., Magdalena (Instituto de Ecología, A.C., 2009)
The municipality of Xico is an important cattle-ranching area located in central Veracruz. Here, an interview was conducted to 48 owners in order to investigate which are the main agricultural and livestock chemical products more often applied. An overall of 1,700 cattle heads was found in the farms sampled. Cattle are treated with commercial antihelmintics containing fenbendazole, ivermectin, albendazole or levamisole as chemical active compounds to prevent and control parasite infestations. Control of flies and ectoparasites is carried out by means of organophosphate and pyrethroid insecticides. Weeds of grasslands are basically manually controlled by hand-cutting although some times organochloride herbicides containing principally picloram+2,4-D or glyphosate are also used. Excessive application of all of these chemicals affects the soil fauna of the grassland, especially the dung beetles that bury the cattle manure, and possibly other soil animals and human beings as well.